Privacy and Biobanking in China: A Case of Policy in Transition. Issue 4 (2015) - Chen, Haidan; Chan, Benny; Joly, Yann
Abstract : With a population of over 1.3 billion, China is the most populous country in the world. It is facing an acute aging population problem, with a projected 440 million residents over age 60 and 101 million over age 80 by 2050. Furthermore, rapid industrialization and urbanization in China have resulted in serious air pollution and associated public health problems, including an increase in respiratory diseases and cancers. These and other demographic trends have generated concerns about the cost of health care and its impact on population health. In recent years, the Chinese government has invested heavily in the fields of translational research and biobanking with the hope that research in both fields can yield effective solutions to improve the public's health and quality of life. The establishment of national biobanks was identified as a major initiative needed for the biomedical industry in the 12th Five-Year National Development Plan of Strategic Emerging Industries promulgated by the State Council in 2012.